Knowledge, attitudes, and practices of healthcare providers in pre-hospital care in Nepal - Pavan Kumar Sah; Wenyi Lai; Neelam Gupta; Bimal Singh Bist; Sanjib Gautam; Khem Raj Sapkota; Bipin Koirala; Ileana Kong Zhuo; Morlai Sesay; Ying Guan; Ying Guan (Frontiers in Public Health)
IntroductionPre-hospital emergency care is crucial for improving patient outcomes, especially in low- and middle-income countries (LMICs) where trauma is a leading cause of death. In Nepal, inadequate pre-hospital care contributes to approximately 16,600 preventable deaths annually. This study assessed the knowledge, attitudes, and practices (KAP) of healthcare providers in pre-hospital care to identify factors influencing their preparedness.MethodsA quantitative, descriptive cross-sectional design was employed, utilizing a 35-item questionnaire based on a 5-point Likert scale. Data were collected via an online survey (Google Forms) from 517 healthcare providers (doctors, nurses, and paramedics) across 16 hubs and 76 satellite hospitals in Nepal’s seven provinces based on a systematic randomization technique. Data were described with median and interquartile range. Nonparametric analysis, rank Spearman’s rank correlation, and ordinal regression were used to analyze the data.ResultsThe study revealed that 62% of providers had good knowledge, 66% exhibited positive attitudes, but only 25% demonstrated good practice. Significant variations were observed by gender, profession, and workplace, with males, doctors, and private hospital providers scoring higher in knowledge and practice. Moderate correlations were found between knowledge, attitude, and practice (rs = 0.420–0.562, p < 0.001). Ordinal logistic regression indicated significant associations between demographic factors and KAP levels.ConclusionDespite good knowledge and positive attitudes, only 25% demonstrated good practice, indicating practical implementation of pre-hospital care remains suboptimal. Targeted training programs, simulation-based learning, and continuous professional development will be needed to bridge the gap between knowledge and practice.